Well London Phase-1: results among adults of a cluster-randomised trial of a community engagement approach to improving health behaviours and mental well-being in deprived inner-city neighbourhoods. Issue 7 (31st January 2014) - Phillips, Gemma; Bottomley, Christian; Schmidt, Elena; Tobi, Patrick; Lais, Shahana; Yu, Ge; Lynch, Rebecca; Lock, Karen; Draper, Alizon; Moore, Derek; Clow, Angela; Petticrew, Mark; et al.
Abstract : Background: We report the main results, among adults, of a cluster-randomised-trial of Well London, a community-engagement programme promoting healthy eating, physical activity and mental well-being in deprived neighbourhoods. The hypothesis was that benefits would be neighbourhood-wide, and not restricted to intervention participants. The trial was part of a multicomponent process/outcome evaluation which included non-experimental components (self-reported behaviour change amongst participants, case studies and evaluations of individual projects) which suggested health, well-being and social benefits to participants. Methods: Twenty matched pairs of neighbourhoods in London were randomised to intervention/control condition. Primary outcomes (five portions fruit/vegetables/day; 5×30 m of moderate intensity physical activity/week, abnormal General Health Questionnaire (GHQ)-12 score and Warwick–Edinburgh Mental Well-being Scale (WEMWBS) score) were measured by postintervention questionnaire survey, among 3986 adults in a random sample of households across neighbourhoods. Results: There was no evidence of impact on primary outcomes: healthy eating (relative risk [RR] 1.04, 95% CI 0.93 to 1.17); physical activity (RR:1.01, 95% CI 0.88 to 1.16); abnormal GHQ12 (RR:1.15, 95% CI 0.84 to 1.61); WEMWBS (mean difference [MD]: −1.52, 95% CI −3.93 to 0.88). There was evidence of impact on some secondary outcomes: reducing unhealthy eating-score (MD: −0.14, 95% CI −0.02 to 0.27) and increased perception that people in the neighbourhood pulled together (RR: 1.92, 95% CI 1.12 to 3.29). Conclusions: The trial findings do not provide evidence supporting the conclusion of non-experimental components of the evaluation that intervention improved health behaviours, well-being and social outcomes. Low participation rates and population churn likely compromised any impact of the intervention. Imprecise estimation of outcomes and sampling bias may also have influenced findings. There is a need for greater investment in refining such programmes before implementation; new methods to understand, longitudinally different pathways residents take through such interventions and their outcomes, and new theories of change that apply to each pathway.